Implementasi Model Project Based Learning (PjBL) pada Materi Pola Bilangan untuk Meningkatkan Pemecahan Masalah Siswa SMP Negeri 1 Pantai Cermin - Sihombing, Heldon; Panggabean, Ellis Mardiana; Naibaho, Tutiarny (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to determine the effect of the Project Based Learning (PjBL) model on students' mathematical problem-solving abilities. This research uses a quantitative approach with a quasi-experimental method. The research sample consists of two eighth-grade classes at SMP Negeri 1 Pantai Cermin, each consisting of 30 students. Class VIII-1 serves as the experimental class treated with the PjBL model, while class VIII-2 serves as the control class using conventional methods. Data were collected through pretest and posttest, then analyzed using normality test, homogeneity test, and t-test. The test results indicate that the data is normally distributed and homogeneous. The t-test shows a significance value < 0.05, which means there is a significant difference between the two classes. The average posttest score of the experimental class (86) is higher than that of the control class (72). These results suggest that the PjBL model has a positive effect on improving students' problem-solving skills.